Three-dimensional structure of a membrane-microtubule complex (The Rockefeller University Press, 1984)
The unicellular algae Distigma proteus contain a group of aligned microtubules associated with their cell membrane. The association is maintained in isolated membrane fragments. The membrane-microtubule complex also includes a crystalline array of membrane particles. The major peptide component of this array was identified by labeling whole cells with radioiodine. The entire complex of membrane, particles, and microtubules is sufficiently well ordered to permit reconstruction from electron micrographs by Fourier techniques. A three-dimensional model of the membrane array at a nominal resolution of 2.5 nm has been calculated. Some similarities were apparent between lattice spacings in the membrane array and in microtubules. Analysis of these lattice correlations suggests a way in which the array of membrane particles may serve as scaffolding for microtubule attachment.